Introduction to petroleum engineering - Fanchi, John R.; Christiansen , Richard L. (Hoboken, New Jersey : Wiley, 2016)
Presents key concepts and terminology for a multidisciplinary range of topics in petroleum engineering -Places oil and gas production in the global energy context -Introduces all of the key concepts that are needed to understand oil and gas production from exploration through abandonment -Reviews fundamental terminology and concepts from geology, geophysics, petrophysics, drilling, production and reservoir engineering -Includes many worked practical examples within each chapter and exercises at the end of each chapter highlight and reinforce material in the chapter -Includes a solutions manual for academic adopters.
About the authors Preface i Chapter 1 Introduction 1 1.1 What is Petroleum Engineering? 1.2 Life Cycle of a Reservoir 1.3 Reservoir Management 1.4 Petroleum Economics 1.5 Petroleum and the Environment 1.6 Activities Chapter 2 The Future of Energy 2.1 Global Oil and Gas Production and Consumption 2.2 Resources and Reserves 2.3 Oil and Gas Resources 2.4 Global Distribution of Oil and Gas Reserves 2.5 Peak Oil 2.6 Future Energy Options 2.7 Activities Chapter 3 Properties of Reservoir Fluids 3.1 Origin 3.2 Classification 3.3 Definitions 3.4 Gas Properties 3.5 Oil Properties 3.6 Water Properties 3.7 Sources of Fluid Data 3.8 Applications of Fluid Properties 3.9 Activities Chapter 4 Properties of Reservoir Rock 4.1 Porosity 4.2 Permeability 4.3
Reservoir Heterogeneity and Permeability 4.4 Directional Permeability 4.5 Activities Chapter 5 Multiphase Flow 5.1 Interfacial Tension, Wettability, and Capillary Pressure 5.2 Fluid Distribution and Capillary Pressure 5.3 Relative Permeability 5.4 Mobility and Fractional Flow 5.5 One-Dimensional Water-Oil Displacement 5.6 Well Productivity 5.7 Activities Chapter 6 Petroleum Geology 6.1 Geologic History of the Earth 6.2 Rocks and Formations 6.3 Sedimentary Basins and Traps 6.4 What do you need to form a hydrocarbon reservoir? 6.5 Volumetric Analysis, Recovery Factor, and EUR 6.6 Activities Chapter 7 Reservoir Geophysics 7.1 Seismic Waves 7.2 Acoustic Impedance and Reflection Coefficients 7.3 Seismic Resolution 7.4 Seismic Data Acquisition, Processing
and Interpretation 7.5 Petroelastic Model 7.6 Geomechanical Model 7.7 Activities Chapter 8 Drilling 8.1 Drilling Rights 8.2 Rotary Drilling Rigs 8.3 The Drilling Process 8.4 Types of Wells 8.5 Activities Chapter 9 Well Logging 9.1 Logging Environment 9.2 Lithology Logs 9.3 Porosity Logs 9.4 Resistivity Logs 9.5 Other Types of Logs 9.6 Log Calibration with Formation Samples 9.7 MWD and LWD 9.8 Reservoir Characterization Issues 9.9 Activities Chapter 10 Well Completions 10.1 Skin 10.2 Production Casing and Liners 10.3 Perforating 10.4 Acidizing 10.5 Hydraulic Fracturing 10.7 Activities Chapter 11 Upstream Facilities 11.1 Onshore Facilities 11.2 Flash Calculation for Separators 11.3 Pressure Rating for Separators 11.4 Single-Phase Flow in Pipe
Performance of Conventional Oil and Gas Reservoirs 14.4 Performance of an Unconventional Reservoir 14.5 Performance of Geothermal Reservoirs 14.6 Activities Chapter 15 Midstream and Downstream Operations 15.1 The Midstream Sector 15.2 The Downstream Sector: Refineries 15.3 The Downstream Sector: Natural Gas Processing Plants 15.4 Sakhalin-2 Project, Sakhalin Island, Russia 15.5 Activities Appendix A Unit Conversion Factors References Index
Keywords: Petroleum engineering; Electronic books